Systematic review and meta-analysis of preterm birth and later systolic blood pressure - de Jong, Femke (2011)
Lower birth weight due to fetal growth restriction is associated with higher blood pressure later in life, but the extent to which preterm birth (<37 completed weeks’ gestation) or very low birth weight (<1500g) predicts higher blood pressure is less clear. We performed a systematic review of 27 observational studies that compared the resting or ambulatory systolic blood pressure, or diagnosis of hypertension, among children, adolescents, and adults born preterm or very low birth weight with those born full term. We performed a meta-analysis with the subset of 10 studies that reported the resting systolic blood pressure difference in mmHg with 95% confidence intervals or standard errors. We assessed methodological quality with a modified Newcastle-Ottawa scale. The 10 studies comprised 1342 preterm or very low birth weight and 1738 full term participants from 8 countries. The mean gestational age at birth of the preterm participants was 30.2 weeks (range, 28.8 to 34.1), birth weight 1280 grams (1098 to 1958), and age at systolic blood pressure measurement 17.8 years (6.3 to 22.4). Former preterm or very low birth weight infants had higher systolic blood pressure than full term infants (pooled estimate 2.5 mmHg, 95% CI: 1.7, 3.3). For the 5 highest quality studies, the systolic blood pressure difference was slightly greater, 3.8 mmHg (95% CI 2.6, 5.0). We conclude that infants who are born preterm or very low birth weight have modestly higher systolic blood pressure later in life, and may be at increased risk for developing hypertension and its sequelae.